Reduction in shock burden with catheter ablation versus escalated antiarrhythmic drug therapy: Insights from the VANISH trial. (19th May 2022) - Samuel, M; Healey, J; Nault, I; Sterns, LD; Essebag, V; Gray, C; Hruczkowski, T; Gardner, M; Parkash, R; Sapp, JL
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): 1. Canadian Institutes of Health Research (CIHR) 2. Additional financial support from St. Jude Medical and Biosense Webster Background: Recurrent shocks for ventricular tachycardia (VT) are associated with an increased risk of heart failure and mortality and have a negative influence on quality of life. Catheter ablation has been shown to improve VT event-free survival in patients with antiarrhythmic drug (AAD)-refractory VT and prior myocardial infarction (MI); however, the effects of ablation on shock burden has yet to be investigated. Purpose: Our primary objectives were to compare the shock-treated VT event burden and appropriate shock burden following randomization to treatment with either catheter ablation or escalated AAD therapy among VT patients with prior MI in the Ventricular tachycardia AblatioN versus escalated antiarrhythmic drug therapy in Ischemic Heart disease (VANISH) randomized trial. Methods: Recurrent event analyses were performed using the intention-to-treat population of the VANISH trial. Shock-treated VT event burden was defined as the total number of VT events treated with ≥1 appropriate internal or external shocks. Appropriate shock burden was defined as the total number of appropriate internal and external shocks delivered, regardless of the number of VT events. All VT events and implantable cardioverter defibrillator (ICD) therapies were adjudicated by reviewers blinded to the treatment allocation. Three recurrent event models were used to compare the shock burden between treatment arms (Anderson-Gill (AG), Frailty, and Prentice, Williams, and Peterson Total Time (PWP-TT). Each model clustered by patient and accounted for competing risk of death with the Fine and Gray sub-distributions hazards model. Results: Of the 259 patients enrolled in the VANISH trial [median age 69.8 (IQR 63.0-74.2) years, 7.0% women], 132 patients were randomized to ablation and 129 patients to escalated AAD therapy. Over a median follow-up of 23.4 (IQR 14.7-40.4) months, there were 138 shock-treated VT events [39.07 (95% CI 33.14-46.07) shock-treated VT events per 100 person-years] in the ablation arm and 218 shock-treated VT events [64.60 (95% CI 56.49–73.84) shock-treated VT events per 100 person-years] in the escalated AAD therapy arm (Figure 1). Ablation patients had a 40% lower shock-treated VT event burden (ie. number of shock-treated VT events) compared to patients randomized to escalated AAD therapy [Figure 1; AG HR 0.60 (95% 0.38-0.95)]. Further, there was also a statistically significant reduction in the appropriate shock burden (i.e. number of appropriate shocks) among ablation patients (169 appropriate shocks) compared to escalated AAD therapy patients (266 appropriate shocks) [Figure 1; AG HR 0.61 (95% CI 0.37-0.96)]. All results were consistent between the 3 recurrent event models. Conclusion: Among patients with AAD-refractory VT and a prior MI, catheter ablation reduced shock-treated VT event burden and appropriate shock burden compared to escalated AAD therapy.